The Piranha Genome Provides Molecular Insight Associated to Its Unique Feeding Behavior. (8th July 2019) - Schartl, Manfred; Kneitz, Susanne; Volkoff, Helene; Adolfi, Mateus; Schmidt, Cornelia; Fischer, Petra; Minx, Patrick; Tomlinson, Chad; Meyer, Axel; Warren, Wesley C
Abstract: The piranha enjoys notoriety due to its infamous predatory behavior but much is still not understood about its evolutionary origins and the underlying molecular mechanisms for its unusual feeding biology. We sequenced and assembled the red-bellied piranha ( Pygocentrus nattereri ) genome to aid future phenotypic and genetic investigations. The assembled draft genome is similar to other related fishes in repeat composition and gene count. Our evaluation of genes under positive selection suggests candidates for adaptations of piranhas' feeding behavior in neural functions, behavior, and regulation of energy metabolism. In the fasted brain, we find genes differentially expressed that are involved in lipid metabolism and appetite regulation as well as genes that may control the aggression/boldness behavior of hungry piranhas. Our first analysis of the piranha genome offers new insight and resources for the study of piranha biology and for feeding motivation and starvation in other organisms.